Renal function and potassium changes in HFrEF patients treated with ACEI vs. ARNI: A prospective cohort study among Acehnese, Indonesia - Munawarah, Iffah; Heriansyah, Teuku; Syukri, Maimun; Purnawarman, Adi; Buchari (Universitas Brawijaya, 2026)
Background: Renin-Angiotensin-Aldosterone System (RAAS) acceleration commonly occur in Heart Failure (HF). Drugs such as Angiotensin-Converting Enzyme Inhibitors (ACEI) and Angiotensin Receptor-Neprilysin Inhibitors (ARNI) become essential part of HF treatment. Long-term consumption may impair kidney function and potassium imbalance, which could potentially limit the therapy, therefore we conducted this study to assess the effects of ACEI and ARNI on renal function and potassium level in Indonesian patients with heart failure with reduced ejection fraction (HFrEF), as no local studies exist. Method: A prospective cohort was performed in Banda Aceh, which comprise of 40 ACEI and 40 ARNI patients on standard therapy. Left ventricular ejection fraction (LVEF), serum creatinine level then converted into estimated Glomerular Filtration Rate (eGFR), and serum potassium level were measured at baseline and after 3 months into the therapy. Independent t-test was applied to compare groups. Result: Both ARNI and ACEI groups showed significant improvement in eGFR (p < 0.005). The intergroup difference was 11 mg/dL (p = 0.038) showed that ACEI had a better outcome in eGFR improvement compare with ARNI. Potassium rose slightly in both groups, with an intergroup difference of 0.082 mmol/L (p = 0.623), indicating no meaningful difference. Conclusion: Both ACEI and ARNI improved eGFR after 3 months, with a modest potassium increase.